ANALYSIS OF SWEET BREEDING VALUE ADDED : (Case Study: UD. Cemarasari, Karangsari Village, Sukorejo, Blitar City) - Anggi Rusita (JOSAR (Journal of Students Academic Research), 2018)
The aim of the study was to find out the benefits obtained from processed starfruit sweets, to know the efficiency of the starfruit candied processing business, and the added value obtained from starfruit candied processing at UD. Cemarasari. The research method used is descriptive method, the type of data uses primary and secondary data. The type of data analysis used is income, efficiency gains, profitability and added value. Where in the end the results were in the form of profits of candied starfruit business in the amount of Rp.137,165.55. R / C is 1.58, with a profitability value of 57.67%, the value of high profitability is influenced by several factors, namely, internal and external factors. And added value of Rp. 12,146.